Designing “pre-reflective” architecture - Andrea Jelić (Ambiances)
The essence of the neurophenomenological “twist” in architecture resides in its particular strength for a more concrete approach to the issue of architectural experience in its multi-sensorial richness. By placing human experience at the centre of architectural design – acknowledging the phenomenal body as the only genuine architectural subject – this specific union of the latest neuroscientific research with the extensive phenomenological legacy can offer valuable insights for interpreting our embodiment and how we relate with our architectural environment. Accordingly, the notion of “pre-reflective” architecture emphasizes the fundamentally embodied and largely pre-conscious interdependence of architectural spaces and our perceptual experience. In a nutshell, the neurophenomenological investigations of architecture aim to identify and approximate the conditions of embodied experience of architecture, while revealing that a purely conceptual engagement with architectural spaces is only a misconception. Also, it raises awareness of the embodied nature of the design process itself, and the need to be attentive to the discordance between the architectural tools for design and representation, designed on the basis of a physical-mathematical conception of space, and the spatiality of the phenomenal world in which we live.